Faktor Risiko Kejadian Hipertensi dalam Kehamilan pada Ibu Hamil di Provinsi Jawa Timur (Analisis Data Riset Kesehatan Dasar Tahun 2018) - Firjatillah, Putri Amalia; Ronoatmodjo, Sudarto (UI Scholars Hub, 2025)
Hypertension during pregnancy is one of the most common pregnancy complications and the leading cause of maternal mortality in Indonesia. One of the regions in Indonesia with a high number of hypertension-related pregnancy complications is East-Java Province with a prevalence rate of 17,8%. This study aims to analyze the risk factors associated with hypertension during pregnancy among pregnant women in East Java. The study adopts a cross-sectional design using secondary data from 758 pregnant women aged 15-54 years in East Java Province who participated in 2018 Riskesdas Survey during which blood pressure measurements were taken. The dependent variable analyzed in this study is hypertension during pregnancy while the independent variables include age, residence, occupation, education level, gravidity status, and history of abortion. The results of this study showed that prevalence of hypertension during pregnancy in East Java Province is 9,9%. The variables of age, occupation, education level, gravidity status, and history of abortion were found to have no significant association with the occurrence of hypertension during pregnancy. The most significant factor associated with hypertension during pregnancy in East Java is residence. Pregnant women in rural areas are 1,771 times more likely to have hypertension during pregnancy than those living in urban areas (aPOR = 1.77; 95% CI = 1.08-2.88). Prevention and control of hypertension during pregnancy programs are very important. The government needs to improve the quality of health facility infrastructure and the distribution of health workers in rural areas.